The Impact of ROA, BOPO, and FDR to Indonesian Islamic Bank's Mudharabah Deposit Profit Sharing - Laila Mugi Harfiah; Atiek Sri Purwati; Permata Ulfah (Faculty of Economic and Business, 2016)
This study aims to determine the effect of profitability ratio (ROA) the cost-revenue ratio (BOPO) and financing to deposit ratio (FDR) toward profit sharing of time deposit mudharaba in Islamic banking in Indonesia. This research is a quantitative study using heading the entire population of Islamic banks in Indonesia and the sample was selected using purposive sampling method. Samples were obtained at 7 Islamic banks and research data in the form of quarterly reports Islamic Banks 2011-2014 period. The analysis namely with the used is a multiple linear regression analysis. The results of the data analysis showed that ROA, BOPO and FDR significant positive effect on the level of profit sharing of time deposit mudharaba. Is divided in changes in the rise and fall rate for the time deposits mudharaba can be explained 47.9 percent by ROA, BOPO and FDR, while 52.1 percent can be explained by other variables not examinedDOI: 10.15408/etk.v15i1.3109